Non-destructive thickness measurement of Si wafers via optical third-harmonic generation with femtosecond laser pulses - In Jae Lee; Dae Hee Kim; Jiwon Hahm; Hongki Yoo; Seung-Woo Kim; Young-Jin Kim (Results in Optics)
Si wafers are vital substrate materials in semiconductor manufacturing and require precise non-destructive thickness measurements. However, the conventional electrical and optical measurement techniques are limited by depth selectivity and system complexity. Here, we propose a simple, high-precision, non-destructive thickness measurement method based on surface-sensitive optical third-harmonic generation at both sides of Si wafers. We irradiated a highly stabilized near-infrared femtosecond pulse laser with a broad spectrum and central wavelength of 1550 nm on the Si wafers, which are non-transparent in the visible to ultraviolet wavelength range. Using the proposed system, the thickness of the certified reference wafer was measured, yielding results that fall within the certified uncertainty.